Efecto de la suplementación de microorganismos benéficos de montaña como probiótico en bovinos de leche. - Zapata Tapia, Víctor Aníbal (2022)
The current research was carried into Quinta Mi Carmencita, located into Aloasi Pichincha province. The research focuses onto bibliographic information review and analysis, and laboratory results about the efficient mountain microorganisms and their application for the cattle health dedicated to dairy production pathogenic microorganisms control and cows nutritional benefit, where are enunciated microorganisms, which promote bovines better ruminal digestion, favor nutrition, growth and animals development, better quality into production standards, digestive tract diseases, less presence by pathogenic microorganisms and they allow stool substance decomposition greater case to get better, within the used methodology it was made a review and compilation of related scientific articles with the topic in the Scopus, Elsevier repositories that allowed the efficient, effective and mountain microorganisms use and application analysis, concluding, what they are beneficial for the animals, by helping to the ruminal pH regulation, better nutrition, nutrient absorption, pathogenic microorganisms control, by solubilizing nutrients for the dairy cows nutrition, and above all, returning the soil microbiological life